Sentimental analysis of customer product Reviews to understand customer needs using machine learning - Symum, Md Abdullah Al; Sheemu, Subarna Yeasmin; Asif, Abu Saleh Md.; Islam, Konika (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.